The influence of training and mental skills preparation on injury incidence and performance in marathon runners - Hamstra-Wright, K. L.; Coumbe-Lilley, J. E.; Kim, H.; McFarland, J. A.; Huxel Bliven, K. C. (The Journal of Strength and Conditioning Research, 2013)
There has been a considerable increase in the number of participants running marathons over the past several years. The 26.2-mile race requires physical and mental stamina to successfully complete it. However, studies have not investigated how running and mental skills preparation influence injury and performance. The purpose of our study was to describe the training and mental skills preparation of a typical group of runners as they began a marathon training program, assess the influence of training and mental skills preparation on injury incidence, and examine how training and mental skills preparation influence marathon performance. Healthy adults (N = 1,957) participating in an 18-week training program for a fall 2011 marathon were recruited for the study. One hundred twenty-five runners enrolled and received 4 surveys: pretraining, 6 weeks, 12 weeks, posttraining. The pretraining survey asked training and mental skills preparation questions. The 6- and 12-week surveys asked about injury incidence. The posttraining survey asked about injury incidence and marathon performance. Tempo runs during training preparation had a significant positive relationship to injury incidence in the 6-week survey (?[93] = 0.26, p = 0.01). The runners who reported incorporating tempo and interval runs, running more miles per week, and running more days per week in their training preparation ran significantly faster than did those reporting less tempo and interval runs, miles per week, and days per week (p ? 0.05). Mental skills preparation did not influence injury incidence or marathon performance. To prevent injury, and maximize performance, while marathon training, it is important that coaches and runners ensure that a solid foundation of running fitness and experience exists, followed by gradually building volume, and then strategically incorporating runs of various speeds and distances.